Analisis Respon Guru Sekolah Dasar Pada Live Chat Streaming (Study Refleksi Pelaksanaan Seminar Dalam Jaringan) - Ali, Andi Muhammad; Safiudin, Safiudin; Akbar, Azaz; Sabillah, Bellona Mardhatillah (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2021)
The rise of online seminars being held, of course, has advantages and disadvantages. Therefore it needs to be answered in a study. This type of research is a qualitative research method using a survey method. The research variables were the response of elementary school teachers and live chat streaming services. Subjects in this study were elementary school teachers who attended online seminars who were selected using simple random sampling. Data is taken and analyzed from teacher comments on google forms and live chat streaming on YouTube. The survey results show that descriptively elementary school teachers are enthusiastic about participating in online seminars via live chat streaming.